Serum and Saliva Sialic Acid in Periodontitis Patients with and without Cardiovascular Disease - ALTURFAN, EBRU IŞIK (KARGER, 2009)
Serum total sialic acid (sTSA) has recently been shown to be a cardiovascular risk factor. However, there is little information about the role of sTSA and TSA in saliva in periodontitis, a chronic and inflammatory disease known to be a risk factor for cardiovascular disease (CVD). We aimed to investigate the changes in sTSA and TSA levels in saliva in patients having both periodontitis and CVD versus periodontitis patients without diagnosed CVD. The study group consisted of 26 patients with proven periodontitis and 26 controls with no diagnosed systemic disease but periodontitis. sTSA and saliva TSA levels were determined by the thiobarbituric acid method, and C-reactive protein (CRP) was evaluated by the nephelometric method. The severity of periodontitis has been determined by the community periodontal index of treatment needs (CPITN). TSA in blood and saliva and CRP levels in blood were significantly increased in CVD patients compared with the control group. CPITN ranged from 2 to 4 in both groups. Significant and positive correlations were found between sTSA and saliva SA levels in patients and controls and between tooth loss and TSA both in blood and saliva. Therefore, TSA in saliva may be a useful marker similar to sTSA in CVD patients. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Cardiovascular disease; Inflammation; Periodontitis; Saliva; Sialic acid; C-REACTIVE PROTEIN; ATHEROSCLEROSIS; INFLAMMATION; INFECTIONS; CELLS